Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 49



Work Step by Step

We first use the FOIL method to simplify the expression. Then, knowing that $i=\sqrt{-1}$, we can substitute $-1$ for $i^{2}$ to obtain: $(4-3i)(1-2i)$ =$4(1-2i)-3i(1-2i)$ =$4-8i-3i+6i^{2}$ =$4-11i+6i^{2}$ =$4-11i+6(-1)$ =$4-6-11i$ =$-2-11i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.